Qualidade da água para consumo humano na Paraíba: sistemas de Informações para fins de vigilância e controle das doenças diarreicas agudas - Pachá, Anna Stella Cysneiros (2018)
Water is an essential element to life and must be free of toxins and microorganisms to have their characteristics preserved. The disorderly growth of populations, natural and socio-cultural factors, has caused serious problems to the environment, causing water scarcity and degradation of water sources, generating water management challenges and threatening environmental sustainability, socioeconomic development and quality of life. Diarrheal disease is the second leading cause of infant death in the world and in Brazil, largely due to poor water quality. According to DATASUS / MS, in the years 2013 and 2014, there were 483,117 hospitalizations and 104,232 deaths from diarrhea in the country, with 26.35% of deaths in the Northeast region. OBJECTIVE: To identify risk factors from alternative collective sources, populations vulnerable to illness, to evaluate the correlation between water consumption from Collective Alternative Solutions (SAC), whose quality is monitored by SISAGUA and the occurrence of Acute Diarrheal Diseases (DDA) in the State of Paraíba. METHODOLOGY: Data were analyzed using descriptive statistics, in an interdisciplinary way and addressing environmental indicators and parameters related to water quality (SISAGUA), the information concerning the municipalities of Paraíba with incidence rates of ADI (SIVEP_DDA) was analyzed above 30,000 cases / 100,000 inhabitants, in the period from 2012 to 2016. RESULTS: Positive correlation was evidenced for the municipality of Guarabira. The other variables were unsatisfactory for the other municipalities. We also used maps for georeferencing of sources registered in SISAGUA. However, the incidence of ADI remained high throughout the study. CONCLUSION: The data studied indicated the underutilization of SISAGUA and SIVEP_DDA, but they are viable and strategic information systems for municipal management, making possible through the results to guide intersectoral actions of health surveillance, enabling the improvement in the quality of life of the population that use SAC in the state of Paraíba.